Meningkatkan Inovasi dan Kreatifitas Pembelajaran Berdiferensiasi dengan Fasilitasi Merdeka - Siti Wahyuningsih; Sunarti Sunarti (UM Purwokerto Press, 2023)
The implementation of education in schools turns out to be the responsibility of teachers. The learning activities carried out by teachers are expected to serve as a gateway of knowledge, skills, and character excellence as planned in the curriculum. Teachers have the task to serve students with all their diversity and to provide the best learning environment and experiences for them. Teachers need to enhance their ability to create and develop more creative and effective learning methods in facilitating students to achieve learning goals. Teacher innovation can be done in various ways, such as creating interesting and interactive lesson plans, using technology in learning, establishing good communication with students and parents, and improving educational skills and developing students' skills. Teacher innovation can be seen in new methods or modifications on available methods, making learning more effective and efficient. Teacher creativity is the ability of teachers to utilize the resources they have to design and support the learning process so that it becomes interesting and meets the learning needs of students. Differentiated learning is an approach that considers differences in student abilities and needs within a class. There are three differentiation strategies that can be employed: content differentiation, process differentiation, and product differentiation. Fasilitasi Merdeka is a method used to enhance innovation and creativity of First and Fourth grade teachers in the Daerah Binaan (Supervisory Area), Rowokele sub-district in preparing and implementing the flow of Social Studies learning. The Fasilitasi Merdeka method adopts the flow of Merdeka in Pioneer Teacher Education with some modifications in its process. The Alur Merdeka referred to an abbreviation for Mulai dari diri (Self-Starting), Eksplorasi Konsep (Concept Exploration), Ruang Kolaborasi (Collaboration Space), Demonstrasi Kontekstual (Contextual Demonstration), Elaborasi Pemahaman (Understanding Elaboration), Koneksi antar materi (Connection between Materials), and Aksi Nyata (Real Action). The improvement of teachers' ability in planning and implementing learning increased from the average of 62% to 78%, or increasing 16%. The improvement of teachers' creativity in planning and implementing learning increased from the average of 71% to 80%, or increasing 9%. The improvement of teacher innovation in learning innovation increased from the average of 47% to 68%, or increasing 21%.